Freight trains dynamics: effect of payload and braking power distribution on coupling forces. Issue 1 (2nd January 2017) - Cheli, F.; Di Gialleonardo, E.; Melzi, S.
ABSTRACT: Coupling forces, especially buffer forces, play a significant role in affecting running safety of freight trains. The increase in coupling force is due to relative motion between adjacent wagons that depends both on track geometry and on manoeuvre performed. Emergency braking in particular, can strongly excite the longitudinal dynamics of a trainset, usually causing significant solicitations on coupling elements. Additionally, braking while cornering may enhance the effect of the coupling forces on the lateral dynamics of the wagon, decreasing running safety margins. A factor that affects the maximum solicitations on coupling devices during emergency braking is payload distribution compared to brake power distribution along the trainset. This issue is particularly significant in Italian railways where empty wagons may be placed along the trainset between fully laden ones without any particular restriction. This paper presents the results of a research aiming at defining imbalance indexes which can be related to the maximum forces exchanged among wagons through the coupling devices. Indexes can be used as guidelines for identifying critical payload distributions and improve wagons arrangement.